Renewable Power Potential from Municipal Solid Waste: A Case Study in Jiangxi, China - Rafiq Muhammad Aftab (SAGE Publishing, 2021)
Development of renewable energy is important to modern society because climate change induced from fossil use has resulted in severe and possibly irreversible environmental impacts such as sea level rise, desertification, diminished land productivity, and increased possibility of extreme events. Therefore, the utilization of renewable and clean energy not only increases regional energy security but also alleviate the environmental risk. In this study, we employ the lifecycle assessment to examine the electricity generation from the use of municipal solid waste in China, and then investigate the emission reduction from this application. Different supply patterns of the wastes are also compared to make the results more robust. The results show that if recycled wastes are fully utilized, approximately 11,107 GWh can be generated, along with a profit of $1.2 billion from energy sales. In this case, the CO 2 emission will reduce by 9.7 million metric tons. If the food waste is used in compositing and animal feed, the net power generation and emission reduction are about 8,216 GWh and 7.32 million metric tons, respectively. If additional 30% of recycled wastes are assumed to be utilized in their past use, the power generation, profit, and emission reduction will further decrease to 5,750 GWh, $697 million, and 5.12 metric tons, respectively. The results point out that the utilization of recycled wastes can effectively reduce the reliance on fossil fuels, improve energy security, and increase social welfare. Insights of the results and policy implications are also discussed in detail.